2016
DOI: 10.1002/jcb.25537
|View full text |Cite|
|
Sign up to set email alerts
|

γ‐Secretase Dependent Nuclear Targeting of Dystroglycan

Abstract: Dystroglycan is frequently lost in adenocarcinoma. α‐dystroglycan is known to become hypoglycosylated due to transcriptional silencing of LARGE, whereas β‐dystroglycan is proteolytically cleaved and degraded. The mechanism and proteases involved in the cleavage events affecting β‐dystroglycan are poorly understood. Using LNCaP prostate cancer cells as a model system, we have investigated proteases and tyrosine phosphorylation affecting β‐dystroglycan proteolysis and nuclear targeting. Cell density or phorbol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Thus, we hypothesize that proteolysis of the -Dg ectodomain [38] or of -Dg's N-terminal portion [39][40][41] produced by Matrix MetalloProteinases (MMP) Furin andsecretase [42], respectively, may contribute to the pathophysiology of the AML, as these have been implicated in cancer progression in other systems [43,44]. Recently, it was established that hypoglycosylation severely alters -Dg's capability to bind to ECM partners, facilitating its degradation by MMP-2 or by other enzymes not identified to date [45]; additionally, in some patients affected by dystroglycanopathy, an important reduction of the Dg core protein was identified [46].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize that proteolysis of the -Dg ectodomain [38] or of -Dg's N-terminal portion [39][40][41] produced by Matrix MetalloProteinases (MMP) Furin andsecretase [42], respectively, may contribute to the pathophysiology of the AML, as these have been implicated in cancer progression in other systems [43,44]. Recently, it was established that hypoglycosylation severely alters -Dg's capability to bind to ECM partners, facilitating its degradation by MMP-2 or by other enzymes not identified to date [45]; additionally, in some patients affected by dystroglycanopathy, an important reduction of the Dg core protein was identified [46].…”
Section: Discussionmentioning
confidence: 99%
“…but also in the post-transductional levels (Sgambato et al, 2007). Also, studies suggested that there were possible posttranscriptional mechanisms, such as proteolitic enzymes which could modulate the DG expression as well as its link with the basal lamina in cancer (Bao et al, 2009;Leocadio et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mammalian system suggest that proteolysis, tyrosine phosphorylation, and translocation of Dg to the nucleus result in altered gene transcription [110]. A recent study in prostate cancer cells showed cell densitydependent γ-secretase and furin-mediated proteolysis of β-dystroglycan which could be stimulated by Notch, leading to nuclear targeting [111]. Another work uncovered the mechanism of retrograde trafficking of βdystroglycan from the plasma membrane to the nucleus [112].…”
Section: Nuclear Proteinsmentioning
confidence: 99%